Peranan Inovasi untuk Memajukan Bisnis Start Up dalam Kegiatan Perekonomian di Indonesia - Irvan Affandi; Farhan Farhan; Dita Marsela Saragih; Lokot Muda Harahap (Jurnal Manajemen Bisnis Digital Terkini, 2025)
This study aims to determine the role of innovation in developing start-up businesses. This study uses a descriptive research method. This method aims to describe and analyze the role of innovation in developing start-up businesses. This research discusses the role of innovation in developing start-up businesses, covering aspects of product development, marketing, and management that can provide added value and create new markets. Start-ups in Indonesia, especially internet-based ones, are growing rapidly due to technological advances and the increase in internet users in almost all walks of life. Innovation plays a key role in the world of entrepreneurship because it drives business growth and development, increases competitiveness, and creates new value for customers. Innovation is a key element for entrepreneurs who want to survive and thrive in this era of globalization and digitalization. Start-up businesses must continue to innovate in their products, services, and business models in order to compete in a dynamic market. Innovation allows companies to create added value for customers and deliver new solutions that are better than competitors.